53BP1‐mediated recruitment of RASSF1A to ribosomal DNA breaks promotes local ATM signaling. (27th June 2022) - Tsaridou, Stavroula; Velimezi, Georgia; Willenbrock, Frances; Chatzifrangkeskou, Maria; Elsayed, Waheba; Panagopoulos, Andreas; Karamitros, Dimitris; Gorgoulis, Vassilis; Lygerou, Zoi; Roukos, Vassilis; O'Neill, Eric; Pefani, Dafni Eleftheria
Abstract: DNA lesions occur across the genome and constitute a threat to cell viability; however, damage at specific genomic loci has a relatively greater impact on overall genome stability. The ribosomal RNA gene repeats (rDNA) are emerging fragile sites. Recent progress in understanding how the rDNA damage response is organized has highlighted a key role of adaptor proteins. Here, we show that the scaffold tumor suppressor RASSF1A is recruited to rDNA breaks. RASSF1A recruitment to double‐strand breaks is mediated by 53BP1 and depends on RASSF1A phosphorylation at Serine 131 by ATM kinase. Employing targeted rDNA damage, we uncover that RASSF1A recruitment promotes local ATM signaling. RASSF1A silencing, a common epigenetic event during malignant transformation, results in persistent breaks, rDNA copy number alterations and decreased cell viability. Overall, we identify a novel role for RASSF1A at rDNA break sites, provide mechanistic insight into how the DNA damage response is organized in a chromatin context, and provide further evidence for how silencing of the RASSF1A tumor suppressor contributes to genome instability. Synopsis: RASSF1A tumor suppressor is recruited to ribosomal DNA breaks in a 53BP1‐dependent manner to promote local ATM signaling, rDNA break repair and cell survival. The ribosomal DNA (rDNA) repeats are an unstable area of the genome vulnerable to damage and recombination. The adaptor protein RASSF1A co‐localizes with translocated rDNA breaks at the nucleolar periphery. RASSF1A recruitment to rDNA breaks depends on its interaction with 53BP1 and facilitates local ATM signaling. Depletion of RASSF1A results in persistent breaks and reduces cell survival in response to rDNA damage Abstract : RASSF1A tumor suppressor is recruited to ribosomal DNA breaks in a 53BP1‐dependent manner to promote local ATM signaling, rDNA break repair and cell survival.